2021
DOI: 10.1038/s41467-021-24137-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional super-enhancers control cancer stemness and metastasis genes in squamous cell carcinoma

Abstract: Cancer stem cells (CSCs) play a critical role in invasive growth and metastasis of human head and neck squamous cell carcinoma (HNSCC). Although significant progress has been made in understanding the self-renewal and pro-tumorigenic potentials of CSCs, a key challenge remains on how to eliminate CSCs and halt metastasis effectively. Here we show that super-enhancers (SEs) play a critical role in the transcription of cancer stemness genes as well as pro-metastatic genes, thereby controlling their tumorigenic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 37 publications
5
55
0
Order By: Relevance
“…While the role of PogZ in cancer is poorly understood, this protein was reported to interact with HRP2 in cancer cells to facilitate DNA repair [29,63]. Med-1, a mediator of RNAPII transcription and interactor of the bromodomain protein 4 (BRD4), an SE assembly protein, was recently implicated in leukemia chemoresistance via interaction with LEDGF/p75 [15] and in enhancing the stemness and metastasis of squamous cell carcinoma via SE formation [64].…”
Section: Discussionmentioning
confidence: 99%
“…While the role of PogZ in cancer is poorly understood, this protein was reported to interact with HRP2 in cancer cells to facilitate DNA repair [29,63]. Med-1, a mediator of RNAPII transcription and interactor of the bromodomain protein 4 (BRD4), an SE assembly protein, was recently implicated in leukemia chemoresistance via interaction with LEDGF/p75 [15] and in enhancing the stemness and metastasis of squamous cell carcinoma via SE formation [64].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the staining declines toward the tumor center [36,81]. Moreover, higher FOSL1 levels may indicate the presence of metastases since specimens taken from patients with metastases in the liver [36] and the lymph nodes [82] exhibit more intense staining for FOSL1 than the tumor samples taken from the patients that do not have metastases.…”
Section: Role Of Fosl1 In Tumorigenesis 41 Fosl1 Expression Pattern I...mentioning
confidence: 99%
“…Finally, investigations have shown that SEs are crucial for the survival of HNSCC cancer stem cells. Perturbation of SE-mediated transcription led to the elimination of these cells [46]. CDK7 overexpression has been observed in many cancer entities and generally indicates a worse prognosis and is associated with aggressive clinicopathological features.…”
Section: Discussionmentioning
confidence: 99%